Treatment of leachate from Bantargebang Landfill using oxidation with H2O2 - Riang Ursada; Zahid Jidan Alfani; Arseto Yekti Bagastyo (Center for Science and Technology, IAIN Surakarta, 2023)
Leachate produced from old landfills has a low level of biodegradability making it suitable for physico-chemical treatment. A low level of biodegradability is characterized by a concentration ratio of BOD5/COD ≤ 0.1. The leachate at the Bantargebang Integrated Waste Management Unit (UPST) has a BOD5/COD concentration ratio of 0.05. The current state of processing leachate at the wastewater treatment plant (IPAS) employs biological processing technology. This research uses inlet leachate from IPAS 3 UPST Bantargebang, with a batch system reactor. The reactor is a glass beaker with a capacity of 1 L, operated using a magnetic stirrer with a stirring speed of 200 rpm. The reactor is covered with aluminum foil to prevent oxidation caused by light. The dosage used is based on H2O2/COD concentration ratios, which are 1.0625 and 2.125. Reactions time applied are 60 minutes and 180 minutes. The initial pH levels of the leachate used are 5, 6, 7, and 8. The variations that have optimum values are at pH 6, H2O2/COD 2.125, and a 60-minute reaction time, resulting in average color removal, BOD5, COD, TSS, TN, and H2O2 reacted by 65%.